Molecular docking of 1,3,4-oxadiazoles: a step toward novel tuberculosis therapies - Ali, Yousef; Abd Razik, Basma; Obaid, Ali (Pharmakeftiki, 2025)
Tuberculosis remains a major global health challenge, especially with the rise of multidrug-resistant strains that demand new treatment strategies. One promising target is the Mycobacterium protein-tyrosine-phosphatase B (MptpB), which helps Mycobacterium tuberculosis evade the immune system. This study explores the potential of 1,3,4-oxadiazole derivatives as inhibitors of MptpB. Using advanced molecular docking techniques, four derivatives of 5-(thiophen-2-yl)-1,3,4-oxadiazole-2-amine were designed and evaluated. These compounds were assessed for their ability to bind to the active site of MptpB. Among them, two showed significant potential, with compound #1 achieving a docking score of -8.8 kcal/mol; the highest in the study. Detailed interactions, including multiple hydrogen bonds and hydrophobic contacts, suggest strong binding affinity and stability within the active site. The findings highlight these compounds as promising candidates for new tuberculosis treatments, addressing the urgent need for innovative approaches to combat resistant strains. Further experimental validation and biological studies are necessary in order to translate these computational insights into practical therapeutic applications.